Application of Intermediate Moment-Resisting Frame for Seven-Story Hotel Structure Building in Pontianak - Figo, Luis; Yusuf, Muhammad; Supriyadi, Asep (Fakultas Teknik Universitas Tanjungpura, 2025)
As part of the city